METHODOLOGICAL ASPECTS OF DEVELOPING A BUSINESS PROCESS MANAGEMENT MECHANISM FOR LARGE-SCALE AGRICULTURAL ENTERPRISES - Varfaliuk , В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article explores the methodological aspects of establishing a business process management mechanism in large-scale agricultural enterprises. It characterises the unique features of business processes in this sector, highlighting that these processes in Ukraine's large agricultural firms are influenced by the specific conditions of agriculture, economic factors, and climatic conditions. Additionally, they integrate advanced technology with traditional agricultural practices. The author defines "business process management of large-scale agricultural enterprises" as the purposeful influence of the management system on business processes to optimise them and achieve the specific business goals of the enterprise. Key factors requiring modern methods in business process management for large-scale agricultural operations are identified. The article organises and describes various business process management methods suitable for large-scale agricultural production, including benchmarking, business process automation, Quality Function Deployment (QFD), reengineering, modeling, management by objectives, Agile methodology, and rapid analysis methods. The study concludes that creating an effective mechanism for managing business processes in large agricultural enterprises necessitates a comprehensive methodological approach. This approach must consider the unique characteristics of agricultural production, seasonality, market challenges, and technological aspects. Proposed methodological elements involve structuring business processes, optimising them using modern information technologies, and integrating strategic planning and control tools. Moreover, the business process management mechanism must address sustainable development requirements, minimise environmental impact, and foster interaction with local communities - factors that significantly influence agricultural producers' market access and reputation. The foundation of this management mechanism includes digitalisation (such as automation and Business Intelligence systems), oversight of operational, management, and support processes, a clear decision-making hierarchy, and the flexibility to adapt to unforeseen circumstances. Special emphasis is placed on adapting modern information technologies to automate management processes effectively.